THE NECESSITY TO INPLEMENT A JOB ANALYSIS SYSTEM WITHIN PUBLIC ADMINISTRATION: THE NECESSITY TO INPLEMENT A JOB ANALYSIS SYSTEM WITHIN PUBLIC ADMINISTRATION - Boteva, Nina (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
Description of the opportunities to improve human resource management in the public sector by introducing a job analysis system to the public administration. Outlining a few guidelines that will facilitate the achievement of the fourth goal of the Strategy for development of the public administration by introducing a job analysis system.